Discovery of a new species of Euphlyctis (Anura: Dicroglossidae) from the western coastal plains of peninsular India - Dinesh, K.p.; Channakeshavamurthy, B.h.; Deepak, P.; Shabnam, A.; Ghosh, Avrajjal; Deuti, Kaushik (Zootaxa, 2022)
The aquatic frog genus ‘Euphlyctis’ is now considered under two separate genera- Euphlyctis Fitzinger and Phrynoderma Fitzinger, with four valid species in each genus, respectively. The current distribution range of the genus Phrynoderma is restricted to peninsular India and Bangladesh, with a probability of availability in Sri Lanka. The genus Euphlyctis has a wide range of distribution from the Arabian Peninsula and the South Asian countries, with a few historical descriptions treated as junior synonyms of the species Euphlyctis cyanophlyctis in India. A new species of skittering frog, Euphlyctis jaladhara sp. nov. is described here from the surroundings of the Thattekad Bird Sanctuary of Kerala, India, which has a predominant distribution in the western coastal plains of peninsular India and some parts of the Western Ghats. The new species has distinct morphological characters and a high genetic distance that distinguishes it from the sympatric species. Discussions are made concerning the validity of the species E. ghoshi and E. kalasgramensis.